A new genus and new species of subfamily Trioxinae (Hymenoptera: Aphidiidae) from the Far East of Russia - Davidian, Elena M. (Zootaxa, 2016)
A new Trioxinae (Aphidiidae) genus Sergeyoxis gen. nov., with type species S. monoceratus sp. nov., is described and illustrated from the Russian Far East. This new genus is closely related to Parabioxys Shi et Chen, 2001, but differs from the latter by the development of a single long process (prong) which is not fused with the sixth sternite, fore wing darkened and narrow, and petiole short. Sergeyoxis gen. nov. differs from the all other trioxine taxa by the presence of mobile unpaired process between two last sternites of metasoma.